Fundus Changes Evaluated by OCTA in Patients With Cerebral Small Vessel Disease and Their Correlations: A Cross-Sectional Study - Fu, Wang; Zhou, Xiaoyu; Wang, Minli; Li, Ping; Hou, Jingjing; Gao, Peng; Wang, Jue (Frontiers in Neurology, 2022)
Objective: To reveal the fundus changes in patients with cerebral small vessel disease (CSVD) utilizing optical coherence tomography angiography (OCTA) and to investigate their correlations. Method: From January 2019 to January 2020, patients diagnosed with CSVD by magnetic resonance imaging (MRI) were enrolled in our study and received fundus examinations using OCTA. CSVD was defined as white matter hyperintensities (WMH), enlarged perivascular spaces (PVS), lacunes, or microbleeds in MR imaging. OCTA parameters included foveal avascular zone (FAZ) areas, retinal nerve fiber layer (RNFL) thickness, capillary densities of the superficial retinal capillary plexuses (SRCP), deep retinal capillary plexuses (DRCP), and the radial peripapillary capillary (RPC) network of the disc. Univariate and multivariate logistic regression analysis were performed to explore the correlation between CSVD and fundus changes. Result: A total of 115 patients (40% male) were enrolled and analyzed, with the mean age of 65.11 ± 11.23 years. After multivariate logistic regression analysis, RPC network density was negatively correlated with severity of deep white matter lesions (DWMLs) (OR: 0.909; 95% CI: 0.828-0.998; p = 0.046) and PVS (OR: 0.881; 95% CI: 0.779-0.995; p = 0.041). Parafoveal vessel densities of the SRCP was independently correlated with lacunes (OR:0.889; 95% CI: 0.817-0.967; p = 0.006). Conclusions: OCTA parameters were correlated with CSVD, implying OCTA as a potential method for screening of CSVD.